Chlamydia trachomatis detection in HIV infected patients using polymerase chain reaction - Shrestha, A; Adhikari, N; Shah, Y; Poudel, P; Acharya, B; Pandey, BD (International Journal of Infection and Microbiology, 2013)
Introduction: Chlamydia trachomatis is a sexually transmitted organism and causes important public health problem in the sexually active age group. Limited studies are found regarding the prevalence of C. trachomatis in Nepal. Moreover, currently there are no any study in Nepal reporting the association of chlamydia and HIV infection. This study attempts to determine the burden of chlamydia on HIV positive patients. Materials and Methods: A total of 117 HIV positive patients visiting a HIV clinic in Kathmandu, were screened for chlamydia infection. For this, urine samples were collected and analyzed using the Polymerase Chain Reaction Technique (PCR). Results: C. trachomatis was detected in 4.2% of the total 117 HIV patients. Out of positive cases 60% were males and 40% were females. However, chlamydia was found more prevalent among females (6.8%) than males (3.4%). Eighty percent of positive cases were asymptomatic. Conclusions: Although, the prevalence of chlamydia infection was found less HIV patients, most of those cases were asymptomatic. Therefore, routine checkup is recommended for all suspected cases for timely management of the disease. DOI: http://doi.dx.org/10.3126/ijim.v2i1.8003 Int J Infect Microbiol 2013;2(1):12-16